2011
DOI: 10.1270/jsbbs.61.347
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Aegilops tauschii drought tolerance traits to breeding of hexaploid wheat

Abstract: Few genes are available to develop drought-tolerant bread wheat (Triticum aestivum L.) cultivars. One way to enhance bread wheat’s genetic diversity would be to take advantage of the diversity of wild species by creating synthetic hexaploid wheat (SW) with the genomic constitution of bread wheat. In this study, we compared the expression of traits encoded at different ploidy levels and evaluated the applicability of Aegilops tauschii drought-related traits using 33 Ae. tauschii accessions along with their corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
0
46
1
1
Order By: Relevance
“…tauschii has the least diversity (Dubcovsky and Dvorak, 2007) there by acts as a potential barrier for its improvement. The availability of few genes for developing drought tolerant wheat cultivars has compelled the wheat breeders to use the genetic diversity of wild species to achieve their goals (Sohail et al, 2011). In this regard Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tauschii has the least diversity (Dubcovsky and Dvorak, 2007) there by acts as a potential barrier for its improvement. The availability of few genes for developing drought tolerant wheat cultivars has compelled the wheat breeders to use the genetic diversity of wild species to achieve their goals (Sohail et al, 2011). In this regard Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional breeding approaches has little affect because drought tolerance is a quantitative trait and through selection high level of heritability is needed for the improvement of yield under such circumstances (Sohail et al, 2011). So among other approaches for wheat improvement the use of wild relatives as a source of rich genetic variation has significantly triggered the process (Ashraf, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth performance of the parental Ae. tauschii accessions and their derivative SHWs was then compared (Table 25.1 ; Sohail et al 2011 ). Under well-watered conditions, intercellular CO 2 , transpiration rate, root dry weight and water use effi ciency were signifi cantly correlated in both diploid and hexaploid plants.…”
mentioning
confidence: 99%
“…Several studies revealed the high level of genetic diversity of Ae. tauschii regarding several useful traits, i.e., seed storage protein [4], flowering time [5], disease resistance [6] and biotic and abiotic stress tolerance [7] [8], suggesting the usefulness for improvement of wheat production.…”
Section: Introductionmentioning
confidence: 99%